Case report on sickle cell anemia: a cascade of crisis - Raundhal, Akshay; Menon, Lakshmi; Umalkar, Shriya (International Journal of Contemporary Pediatrics, 2024)
Children with sickle cell homozygous state often experience complications like an acute painful crisis, dactylitis, severe anemia, sequestration, acute febrile illness, and stroke because of its complicated pathophysiology. This is one of the main reasons for a child’s frequent hospital visits or admissions, which is a significant cause of its morbidity. This case discussed a 7-year-old male child who presented to the hospital in vaso-occlusive crisis in the form of pain in the right elbow joint, followed by a rare occurrence of deteriorating multiple morbid complications of sickle cell disease in the same patient within a short span of his hospital stay.